2021
DOI: 10.1017/s1463423621000633
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and the great impulse to telemedicine: the basis of the WONCA Europe Statement on Telemedicine at the WHO Europe 70th Regional Meeting September 2020

Abstract: Summary Telemedicine is the use of telecommunication and information technologies to support the delivery of healthcare at a distance, guaranteeing patients healthcare by facilitating access where barriers exist; the COVID-19 pandemic has attracted worldwide interest in this field. The purpose of this paper is to highlight the main pros and cons of telemedicine, which serve as the basis of the WONCA Europe Statement at the WHO Europe 70th Regional Meeting on 14 September 2020. Pros of telemedicine inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In addition, 8.7% (23/265; 95% CI 5.8%-12.7%) of GPs recommended health apps to patients, whereas only 6.0% (16/265; 95% CI 3.7%-9.6%) and 3.7% (10/265; 95% CI 2.0%-6.9%) of other physicians and other health professionals, respectively, recommended these apps. Other sources were given for 19 Univariate analysis revealed that the use of health apps was associated with a young population, mainly female, living in larger cities, and the use of social network(s) (all P<.001). A potential association between health app use and socioprofessional category (P<.001) was also identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 8.7% (23/265; 95% CI 5.8%-12.7%) of GPs recommended health apps to patients, whereas only 6.0% (16/265; 95% CI 3.7%-9.6%) and 3.7% (10/265; 95% CI 2.0%-6.9%) of other physicians and other health professionals, respectively, recommended these apps. Other sources were given for 19 Univariate analysis revealed that the use of health apps was associated with a young population, mainly female, living in larger cities, and the use of social network(s) (all P<.001). A potential association between health app use and socioprofessional category (P<.001) was also identified.…”
Section: Resultsmentioning
confidence: 99%
“…This study was performed prior to the COVID-19 pandemic. During the pandemic period, eHealth, mHealth, and telemedicine were more widely adopted for crisis management and as a preventive measure to increase clinical care [19,20]. Thus, a similar study should be performed to determine the impact of the pandemic on the use of eHealth.…”
Section: Limitationsmentioning
confidence: 99%
“…The Covid-19 pandemic is a global health emergency that has highlighted the need for an innovative technological system to be able to take care of patients with chronic diseases ( 1 , 2 ). Digital transformation was already underway, especially in the field of diabetes, but this global emergency has accelerated this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…142 However, although during the pandemic telemedicine was adopted to limit interaction, it may have negative effects on the quality of the doctor-patient relationship, the quality of physical examination, and provision of care. 143 The exact role of telemedicine in managing future outbreaks is yet to be fully elucidated, but has been a crucial support throughout the pandemic for outbreak-affected nursing homes.…”
Section: On-site Medicalization Outreach Teams and Telemedicinementioning
confidence: 99%